2010
DOI: 10.7326/0003-4819-152-9-201005040-00004
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Herpes Zoster Vaccine in the Shingles Prevention Study

Abstract: Cooperative Studies Program, Department of Veterans Affairs, Office of Research and Development; grants from Merck to the Veterans Affairs Cooperative Studies Program; and the James R. and Jesse V. Scott Fund for Shingles Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 14 publications
9
76
0
2
Order By: Relevance
“…7). The risk of local reactions was higher among participants aged 60-69 years (56.6%) than among subjects aged ≥70 years (39.2%; [45]). Most local reactions were minor and disappeared within 4 days [36].…”
Section: Local Reactions After Vaccination With the Live Hz Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…7). The risk of local reactions was higher among participants aged 60-69 years (56.6%) than among subjects aged ≥70 years (39.2%; [45]). Most local reactions were minor and disappeared within 4 days [36].…”
Section: Local Reactions After Vaccination With the Live Hz Vaccinementioning
confidence: 99%
“…A total of 5 RCTs were included to assess the safety of the live HZ vaccine [36,37,[42][43][44][45]. They vary widely with regard to their consideration of the relevant endpoints and participant numbers.…”
Section: Vaccine Safetymentioning
confidence: 99%
“…22 Regarding safety of the vaccine, multiple studies have shown that Zostavax® is well-tolerated and that side reactions are generally mild. 20,20,[23][24][25][26] However, as the mean follow-up time of the SPS was limited to 3.1 y, 20,21 the duration of the vaccine protection is still unknown. A short-term persistence substudy (STPS) of the SPS recently showed that vaccine efficacy persists for at least 7 y, but also Herpes zoster (HZ) is a common disease among elderly, which may develop into a severe pain syndrome labeled postherpetic neuralgia (PHN).…”
Section: Introductionmentioning
confidence: 99%
“…Rates of serious adverse events, systemic adverse events, hospitalizations and deaths in the SPS were low in vaccine recipients and comparable with those in placebo recipients 22,151,154 . During the first 42 days after vaccination, 24 cases of zoster in placebo recipients were reported and 7 cases in the vaccination group, none of which were caused by vOka 104 .…”
Section: Preventionmentioning
confidence: 72%